Gas explosion analysis of safety gap effect on the innovating FLNG vessel with a cylindrical platform - Li, J.; Ma, G.; Hao, Hong; Huang, Y. (Elsevier, 2016)
© 2016 Elsevier LtdAfter investigating gas dispersion on a cylindrical Floating Liquefied Natural Gas (FLNG) platform (Li et al, 2016), this second article focuses on assessment of gas explosion by using Computational Fluid Dynamics (CFD). Gas explosion simulations are carried out to evaluate the explosion overpressure mitigating effect of safety gap. The Data-dump technique, which is an effective tool in resetting turbulence length scale in gas explosion overpressure calculation, is applied to ensure simulation accuracy for the congestion scenario with safety gap. Two sets of different safety gaps are designed to investigate the safety gap on the cylindrical FLNG platform, the overall results indicate that the safety gap is effective in reducing overpressure in two adjacent congestions. However, for the explosion scenario where the flame is propagating through several safety gaps to the far field congestion, the safety gap mitigates overpressure only in certain explosion protecting targets. Two series of artificial configurations are modeled to further investigate the explosion scenarios with more than two safety gaps in one direction. It is concluded that the optimal safety gap design in overpressure mitigation for the cylindrical FLNG platform is to balance the safety gap distance ratio in the congested regions.